The Dynamics Of Civic Education In Building Social Awareness In The Digital Era - Yuniarto, Bambang; Ramadhan, Ilyasa; Monika, Dea; Luthfiah, Syifa; Laela Sarda, Hitti (Advances In Social Humanities Research, 2024)
Civic education has become an essential component in shaping individuals as active members of society who are aware of their rights and responsibilities. However, in this digital age, technological developments have brought new challenges that impact the way we understand and engage in social life. In this situation, research has focused on civic education programs to educate the public about digital critical skills and ethical principles in the online world. This study aims to investigate and analyze the more profound impact of social media on forming people's civic awareness in the context of the digital age. This research uses qualitative methods, where the data in this study was obtained through interviews with academics in the field of citizenship and looking for data sources in journal articles and related books. The result of this study is that social media has great significance in the context of civic education, which has an impact that can be both positive and negative. That's why it's essential to work together to tackle cyberbullying and promote online safety, with parents, teachers and caregivers having a key role to play in educating children about safe and responsible online behavior.